Respuesta :

Answer:

C.

Step-by-step explanation:

We are given [tex]f,g[/tex] are odd which means:

[tex]f(-x)=-f(x)[/tex]

[tex]g(-x)=-g(x)[/tex]

We can tell if a function,[tex]h[/tex], is even if [tex]h(-x)=h(x)[/tex].

We can tell if a function,[tex]h[/tex], is odd if [tex]h(-x)=-h(x)[/tex].

So let's test your I,II,III.

We will be replacing x with -x to find out.

I.

[tex]p(x)=f(g(x))[/tex]

[tex]p(-x)=f(g(-x))[/tex]

[tex]p(-x)=f(-g(x))[/tex]

[tex]p(-x)=-f(g(x))[/tex]

[tex]p(-x)=-p(x)[/tex]

So [tex]p[/tex] is odd.

II

[tex]r(x)=f(x)+g(x)[/tex]

[tex]r(-x)=f(-x)+g(-x)[/tex]

[tex]r(-x)=-f(x)+-g(x)[/tex]

[tex]r(-x)=-(f(x)+g(x))[/tex]

[tex]r(-x)=-(r(x))[/tex]

[tex]r(-x)=-r(x)[/tex]

So [tex]r[/tex] is odd.

III

[tex]s(x)=f(x)\cdot g(x)[/tex]

[tex]s(-x)=f(-x) \cdot g(-x)[/tex]

[tex]s(-x)=-f(x) \cdot -g(x)[/tex]

[tex]s(-x)=f(x) \cdot g(x)[/tex]

[tex]s(-x)=s(x)[/tex]

So [tex]s[/tex] is even.

So I and II are odd and III is even.

C. is the answer.

The answer will be C
ACCESS MORE